Pengaruh Pemberian Edukasi Berbasis E- Booklet Terhadap Pengetahuan Dan Sikap Remaja Putri Dalam Upaya Pencegahan Anemia Di SMK Bhakti Indonesia Medika - Alvy Nur Hidayati; Ayu Aminatussyadiah; Rara Febrian Aurilawati (Jurnal Pengabdian Bidang Kesehatan, 2026)
A common health problem, especially in developing countries, is anemia. This is common among adolescent girls due to their lack of knowledge about anemia. This puts them at risk of developing anemia, particularly because menstruation is a contributing factor. Providing health education is expected to change behaviors toward a healthy lifestyle and contribute to preventing anemia among adolescent girls. This community service activity was held on May 26, 2026, at SMK Bhakti Indonesia Medika, and was attended by female students of childbearing age. The methods used included lectures, discussions, question-and-answer sessions, and sharing sessions. Pretests and posttests were used as evaluation materials to measure the increase in students' knowledge. The average pretest score was 7, while the average posttest score was 12, indicating a 5 point increase in knowledge about anemia among adolescent girls. The students demonstrated interest and enthusiasm during this activity. The results and conclusions of the e-booklet-based education program proved to be an effective alternative medium for increasing students' knowledge about anemia prevention. It is hoped that similar education can be implemented sustainably to improve the quality of healthy life in adolescent girls.